2016
DOI: 10.1007/s40735-016-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of High-Chromium White Iron Hardfacing Alloys in an Alkaline Solution

Abstract: Hardfacing alloys of high-chromium white irons (HCWI) deposited using welding are well known for their wear resistance. These materials are applied in conditions needing not only wear resistance but also corrosion. In this study, the HCWI alloys were exposed to alkaline solutions of pH 14. Anodic polarization technique was used to study the corrosion behaviour. The experimental results found that corrosion occurs on carbides in preference to the matrix. Pourbaix diagrams of carbides were found to be very usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…HCWCI-3 experienced slightly higher corrosion resistance than HCWCI-1. This influence of Cr on the resistance of the high-chromium cast iron to corrosion was also observed by other researchers [ 51 ].…”
Section: Resultssupporting
confidence: 84%
“…HCWCI-3 experienced slightly higher corrosion resistance than HCWCI-1. This influence of Cr on the resistance of the high-chromium cast iron to corrosion was also observed by other researchers [ 51 ].…”
Section: Resultssupporting
confidence: 84%
“…The Mulliken charges of Cr 3 C 2 are listed in table 4. From experimental findings of Varmaa et al [19] it was observed that the metal alloy carbides exhibited a ratio of 2:1 for Cr:Fe. Hence, in this study the effect of replacing one Cr atom with Fe-atom, out of the three Cr atoms in Cr 3 C 2 will be investigated.…”
Section: Electronic Properties Of Fe-substituted Chromium Carbidesmentioning
confidence: 96%
“…Inclusion of Fe atoms in chromium carbides would change the physical properties of chromium carbides [17,18]. The stability of the chromium carbides containing Fe atoms will also be affected in corrosive environments [19]. However, a systematic theoretical report on how the electronic structures of the chromium carbide phases are modified due to the introduction of Fe into the carbides is not yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for pH 7 NaCl solution, the eutectic martensitic matrix was not stable due to nobler potential of carbides. The carbides corroded in the pH 7 buffer solution same as in the alkaline solution of pH 14 [23,41], whereas the eutectic austenite matrix sample showed nobler potential than a carbide sample as described in the literature [41] after extraction of carbide and eutectic austenite matrix sample in pH 14 solution.…”
Section: Corrosion Analysis Of Carbide and Eutectic Martensitic Matrimentioning
confidence: 99%
“…The study conducted by Salasi et al [23] of cast HCWI in alkaline solution (pH 12) with inclusion of chloride ions found that corrosion of eutectic austenite matrix happened mainly due to localised breakdown of passive layer. The same eutectic austenite matrix in alkaline solution was found to be relatively uncorroded resulting in the corrosion of carbides [23,41].…”
Section: Stability Of Passive Formation Of Matrix and Pourbaix Diagramsmentioning
confidence: 99%